A Microbial World: Could Metagenomic Next-Generation Sequencing Be Involved in Acute Respiratory Failure? - Huang, Chunrong; Chen, Hong; Ding, Yongjie; Ma, Xiaolong; Zhu, Haixing; Zhang, Shengxiong; Du, Wei; Summah, Hanssa Dwarka; Shi, Guochao; Feng, Yun (Frontiers in Cellular and Infection Microbiology, 2021)
Background: The usefulness of metagenomic next-generation sequencing (mNGS) in identifying pathogens is being investigated, the applications of mNGS in respiratory failure remain to be delineated. Methods: 130 patients with respiratory failure were reviewed, 185 specimens including blood, bronchoalveolar lavage fluid (BALF), sputum, pleural effusion, ascitic fluid and urine were tested by mNGS and culture methods. Clinical features and microbes detected were analysed. Results: mNGS outperformed culture method in positive detection rate of Mycobacterium Tuberculosis (MTB) (OR, ∞; 95% CI, 1-∞; P < 0.05), bacteria (OR, 3.72; 95% CI, 2.4-5.78; P < 0.0001), fungi (OR, 4.36; 95% CI, 2.66-7.16; P < 0.0001), mycoplasma (OR, ∞; 95% CI, 3.1-∞; P = 0.001) and virus (OR, ∞; 95% CI, 177.8-∞; P < 0.0001). 20 patients (28 samples) were detected with Pneumocystis jirovecii by mNGS, but not culture method, most of those patients were immunocompromised, sequencing number of Pneumocystis jirovecii was higher in BALF than that in sputum and blood. Reads number of Klebsiella pneumoniae, Acinetobacter baumannii, Candida albicans, cytomegalovirus (CMV) and Herpes simplex virus 1 (HSV1) in BALF were significantly higher than other sample types. We found that orotracheal intubation, Type 2 diabetes mellitus (T2DM) and immunosuppression were associated with higher detection rate of bacteria and virus by mNGS, inflammatory markers were associated with mNGS positive detection rate of bacteria. In addition, we observed preliminary results of pathogen targets NGS (ptNGS). Conclusion: mNGS can identify a wide range of pathogens, especially Pneumocystis jirovecii and viruses, exhibiting potential applications in clinical diagnostics and research.